Analisis Perancangan Customer Relationship Management Berbasis Web pada PT ASP Jakarta - So, Idris Gautama; Sheila, Sheila (Bina Nusantara University, 2011)
The purpose of this thesis is to identify the needs of web-based CRM in PT ASP and also to design the suitable CRM for the company. The research method is by analyzing competitions in the industry with Porterâs five forces analysis and formulating framework in input stage, matching stage, decision stage to choose the best strategy for the company. From the analysis of formulating strategy, it could be concluded that market penetration strategy is the best strategy for PT ASP. Market penetration strategy is an approach of web-based Customer Relationship Management (CRM) to increase service quality for customers and company introduction to broaden community. Web-based CRM design is suitable for PT ASP based on interview conclusion using 5 features (5C) from the 7 features (7C) in web design elements.Â